2016
DOI: 10.1002/2016gl068390
|View full text |Cite
|
Sign up to set email alerts
|

Climate change reduces warming potential of nitrous oxide by an enhanced Brewer‐Dobson circulation

Abstract: The Brewer‐Dobson circulation (BDC), which is an important driver of the stratosphere‐troposphere exchange, is expected to accelerate with climate change. One particular consequence of this acceleration is the enhanced transport of nitrous oxide (N2O) from its sources at the Earth's surface toward its main sink region in the stratosphere, thus inducing a reduction in its lifetime. N2O is a potent greenhouse gas and the most relevant currently emitted ozone‐depleting substance. Here we examine the implications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…While accelerated tropical upwelling enhances transport of N 2 O from its source towards the stratosphere, it reduces its lifetime (e.g. Kracher et al, 2016). The amount of NO x is then affected by a shorter N 2 O residence time causing its lower production via Reaction (R8a), and as a consequence less O 3 loss in the tropical mid-stratosphere.…”
mentioning
confidence: 99%
“…While accelerated tropical upwelling enhances transport of N 2 O from its source towards the stratosphere, it reduces its lifetime (e.g. Kracher et al, 2016). The amount of NO x is then affected by a shorter N 2 O residence time causing its lower production via Reaction (R8a), and as a consequence less O 3 loss in the tropical mid-stratosphere.…”
mentioning
confidence: 99%
“…(2010) and Kracher et al (2016) showed that the accelerated upwelling decreases the residence time of N 2 O in the stratosphere causing lower NO x production and as a consequence lower O 3 loss. For conditions of slower upwelling, the residence time of N 2 O in the stratosphere is expected to be longer, which then causes higher NO x production and higher O 3 loss.…”
mentioning
confidence: 99%
“…However, its role in the global change remains unclear. It has been suggested that the upper atmospheric circulation favors the stratosphere-troposphere exchange in link with climate change through the greenhouse gas N 2 O [30]. In parallel, chemical reactions implying NO in the atmosphere produce a significant production of various nitrous oxide (see The Physical Science Basis.…”
Section: Discussionmentioning
confidence: 99%
“…NO can also be excited into 22 states, see Table (1). The corresponding cross sections come [13] for incident electron energies of 10,20,30,40 and 50 eV, and we performed a logarithmic extrapolation for larger energies. The TRANSSOLO code uses a multi-stream approach [14 -16], which solves the Boltzmann equation for electron transport in the atmosphere.…”
Section: Modelingmentioning
confidence: 99%